Undergraduates’ opinion after 5-year experience with rotary endodontic instruments - Denise Piotto Leonardi; Flares Baratto-Filho; Gisele Aihara Haragushiku; Flávia Sens Fagundes Tomazinho; Maria da Graça Kfouri Lopes; Alexandre Moro (Revista Sul-Brasileira de Odontologia, 2012)
Introduction: Dentistry evolution in the past few years has revolutionized daily practice in some specialties. One of these revolutions has occurred in Endodontics due to the advancement of rotary techniques for root canal preparation and its subsequent incorporation into the teaching of Dentistry undergraduates. Objective: The aim of this study was to report a 5-year experience on the undergraduate laboratorial and clinical use of rotary endodontic preparation at a private university. Material and methods: Data survey was performed by using a questionnaire composed of nine objective questions; the questionnaire was answered by the undergraduates. Results: The results showed a positive acceptance regarding the undergraduate teaching of the rotary technique (94.7%). The following advantages were highlighted: faster root canal preparation (91.6%) and reduction of patient’s stress (80.9%). Conclusion: It can be concluded that the experience with the two undergraduate groups was excellent due to the high acceptance level of the new technique by the students.